A Recombinase Aided Amplification Assay for Rapid Detection of the Klebsiella pneumoniae Carbapenemase Gene and Its Characteristics in Klebsiella pneumoniae - Zhang, Weiwei; Feng, Yanling; Zhao, Hanqing; Yan, Chao; Feng, Junxia; Gan, Lin; Cui, Jinghua; Liu, Shiyu; Zhang, Rui; Du, Shuheng; Li, Nannan; Xu, Wenjian; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Klebsiella pneumoniae carbapenemase genes (blaKPC) play an important role in carbapenem-resistant Enterobacteriaceae in China. A rapid detection method for blaKPC genes and investigations into the molecular characteristics of blaKPC positive Klebsiella pneumoniae were necessary. In this study, an easy and rapid recombinase aided amplification assay (RAA) for blaKPC was established. This protocol could be completed at 39 °C in 15–20 min. The sensitivity of this assay was determined as 48 copies per reaction, and the specificity was 100%. The blaKPC RAA method could be used for clinical diagnosis and epidemiological investigation. Among 801 fecal samples from inpatients, 34 blaKPC positive isolates were identified from each sample, of which 23 isolates were K. pneumoniae. ST11 with blaKPC-2 was the most prevalent type. All these strains were multidrug resistant and carried various virulence genes. Fecal carriage of blaKPC positive carbapenem-resistant K.pneumoniae poses significant challenges for public health control.